Avalia????o do impacto dos riscos operacionais e dos n??veis de controle nas opera????es realizadas, inadimpl??ncia e nos resultados de uma institui????o financeira - Paiva, Daniel Henrique Santana de (2016)
The aim of this work is to evaluate whether risk variables and control directly affect banking activities, and how to affect them before the customers' financing need, and then allow credit expansion without increasing the exposure or the commitment of the National Financial System. For this we used the data model empirically estimated panel, suggested by Hsiao (1986). The sample covered data from a large financial institution in the country every month in 2015, from January to July to 2,093 business units. The main results suggest that risk and control variables affect significantly the "business", the "default" and the "result of the institution." In this line, should seek to identify new indications of operational risk present in the growth of economic activity and new sources of investment and financing with thirdparty funds (read financial institutions) to businesses.